PERANCANGAN DAN PEMBANGUNAN APLIKASI E-COMMERCE PADA TOKO JUALINLAPTOPID: Perancangan dan Pembangunan Aplikasi E-Commerce pada Toko Jualinlaptopid - Syafe'i Hazami; Yulianti (CV. Multi Kreasi Media, 2022)
Electronic commerce is an act of selling or buying and distributing a product, either goods or services by relying on the internet or telecommunications networks. Toko Jualinlaptopid is a company that runs the services of buying and selling used laptops. The sales system used by the Jualinlaptopid store is to collaborate with subscriptions and find new customers to offer and market products or wait for buyers to come directly to the store, this way of selling results in very limited product marketing reach so only a few potential buyers know. Another problem is that buyers have difficulty in obtaining information about the products available at the store, which results in the buying and selling transaction process taking a long time. To provide a solution to these problems, an e-commerce web application is created that can be useful for shop owners so that the product marketing range becomes wider, Buyers will also find it easy to get product information at the store, this will make the buying and selling process go faster. The waterfall method was chosen in the development of this software, PHP as the programming language, MySQL as the database processor. This research produces an e-commerce information system for selling used laptops at the Jualinlaptopid store that can make it easier for shop owners and buyers to carry out buying and selling used laptops.